(untitled) - Sakita, B. (Singapore, 1985)
This book is written for graduate students in physics who have some rudimentary knowledge of experimental particle physics, and an acquaintance wiht quantum fiel theory, including Feynman graphs, and the notion of renormalization. It might sever as a text for a one-semester course beyond quantum field theory. The material, in fact, was taken in part from such a course offered by the author at MIT and at the Institute for High Energy Physics in Beijing.
Keywords: Quantum field theory,Statistical mechanics,Perturbation (Quantum dynamics),Lý thuyết trường lượng tử,Cơ học thống kê,Sự nhiễu loạn (động lực học lượng tử)